(untitled) (Damascus University Journal for engineering sciences, 2025)
Pilot Study to benefit fromthe Biomass Energy of the Household Organic Solid Waste. In this research, a study, design and implementation of an experimental biothermal reactor was conducted to benefit from the biomass energy of organic solid waste and to secure hot domestic water according to local conditions in rural homes, and to produce the organic fertilizer resulting from the aerobic fermentation of solid waste inside this reactor. We have chosen as a model for such gatherings, the village of Barri Al Sharqi, affiliated to Salamiyah city in the Hama governorate, which is an agricultural town - that we obtain the least possible environmental pollution as well as maintain the integrity of soil, water and air, which in turn constitute the three basic elements in our environment. The results were obtained give clear indications that the biothermal reactor has achieved the goal for which it was designed, where the amount of heat stored daily reached (5518 Wh), and it was noted that the temperature of the reactor was not affected by the temperature of the weather but by the fermentation of organic waste, and the temperature of the water within the water tank has reached up to (37C) in winter and to (70C) in summer. Consequently, The energy resulting from the fermentation of the waste and agricultural organic waste was utilized in terms of the temperature reached by the water as well as the clear environmental impact in reducing the amount of waste reaching the landfill and the positive impact resulting from the mitigating of air, soil and groundwater pollution in the landfill area and on the economic side of reducing the cost of collecting and transporting waste and increasing the operating age of the landfill.